A multi-component reaction kinetics model for the hydrothermal liquefaction of carbohydrates and co-liquefaction to produce 5-ethoxymethyl furfural. (1st March 2022) - Chacón-Parra, Andrés; Lewis, David; Glasius, Marianne; van Eyk, Philip
Highlights: Identification and quantification of aqueous phases from the HTL of carbohydrates. Characterisation of solid products (hydrochar) and unreacted cellulose estimation. Multi-component and shrinking core models for the HTL of saccharides. Ethanol as a hydrogen donor co-solvent in co-liquefaction of carbohydrates. Co-liquefaction of biomass to produce 5-ethoxymethyl furfural and ethyl levulinate. Abstract: Hydrothermal liquefaction (HTL) as a waste management technology has been investigated to produce renewable bio-crude and other valuable products from wet biomass and bio-waste. However, carbohydrates as a vital component in biomass have shown to increase the complexity of the process. Undesirable solid yields produced by the carbonisation/re-condensation of reactive carbohydrate intermediates could limit the renewable crude yield and recovery. In the present study, the reaction mechanism and kinetic models for the HTL of monosaccharides and polysaccharides are investigated using gas chromatography–mass spectrometry (GC–MS) and high-performance liquid chromatography (HPLC) to characterise, validate and quantify the most abundant organic species in the aqueous phase. The experimental data and models presented provide an unbiased understanding of the carbohydrate decomposition during HTL conversion, while the analysis of solid products clarifies solid transformations and integrates both phases into a more comprehensive reaction mechanism approach, including a shrinking core model for cellulose. Finally, ethanol and acetic acid were added as co-solvents to elucidate the effects of a fully renewable hydrogen donor solvent system to generate 5-ethoxymethyl furfural and ethyl levulinate (validated with GC–MS), two renewable fuel additives and promising tunable monomers candidates. Experiments were conducted with glucose, fructose, and cellulose in a batch reactor with 20% by mass premixed feedstock at 250 °C and 300 °C.